2010
DOI: 10.1007/s12223-010-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the life cycle dependent post-translation modifications of protein synthesis elongation factor Tu present in the membrane proteome of streptomycetes and mycobacteria

Abstract: We present the results of analysis of membrane phosphoproteomes from individual morphological stages of Streptomyces coelicolor that reflect developmentally dependent heterogeneity and phosphorylation of intrinsic and externally added purified Strepomyces aureofaciens EF-Tu. Fast growing nonpathogenic Mycobacterium smegmatis was used as a non-differentiating actinomycetes comparative model. Streptomycetes membrane fraction was found to contain protein kinase(s) catalyzing phosphorylation of both its own and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…We have recently shown that, in other Streptomycetes strains, EF-Tu is present in various isoforms differing in pI; these isoforms are present among both cytoplasm and membrane-associated factor (Nguyen et al 2005a;Holub et al 2010). For example, in dormant spores of S. coelicolor, which is a close relative of S. lividans, we observed two EF-Tu isoforms that were present in an equimolar ratio (Holub et al 2007); this result is similar to that observed in this study (Figs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have recently shown that, in other Streptomycetes strains, EF-Tu is present in various isoforms differing in pI; these isoforms are present among both cytoplasm and membrane-associated factor (Nguyen et al 2005a;Holub et al 2010). For example, in dormant spores of S. coelicolor, which is a close relative of S. lividans, we observed two EF-Tu isoforms that were present in an equimolar ratio (Holub et al 2007); this result is similar to that observed in this study (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…The samples (100 μg of proteins or 500,000 cpm of pulse-labelled proteins) were absorbed into IPG strips (Immobiline DryStrips, 180 mm) with a nonlinear pH 4-7 gradient (Amersham Biosciences, UK) and rehydrated overnight. The electrophoresis was performed as described previously (Holub et al 2010). The gels were silver-stained according to Rabilloud (1992).…”
Section: D Electrophoresismentioning
confidence: 99%
“…In bacteria, some ribosomal proteins may have modified functions beyond the translation of mRNA into protein (79). Similarly, elongation factor Tu has been identified both as a surface-exposed protein and an essential virulence factor for several bacteria (14,28,35,52). Ribosomes may also be complexed with protein-translocating channels, making them partially exposed to the extracellular environment, which may also cause them to be detected in screens of surface-exposed proteins (57).…”
Section: Discussionmentioning
confidence: 99%
“…The beads are immersed in a liquid medium that allows for easy modification or replacement of nutrients and growth factors, as well as radioactive labelling of proteins and other macromolecules. Cultivation on beads enables studies of differentiation in streptomycetes using molecular biology and global 'omics' techniques, along with the analysis of produced secondary metabolites such as undecylprodigiosin in Streptomyces lividans (Holub et al, 2010;Nezbedova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%